Shapers of Knowledge Management: Culture, Maturity and Dissemination - Lily Regina Arthi S, M. Hema Mary (International Journal of Advanced Science and Technology, 2020)
Academic institutions are the hot beds of knowledge and are instrumental in stimulating as well as conveying knowledge and associated aspects either in raw or processed form to enable useful application for development and growth. Knowledge to travel smoothly necessitates the backing of the organisation and its associates. The culture of the organisation as well as the psychological maturity of its members would shape the propagation of knowledge or otherwise. A study was launched to examine aspects like organisational culture, psychological maturity, knowledge dissemination and knowledge managementin arts and science institutions in Karnataka whereby 452 faculty’s perceptions were analysed through the application of regression, ANOVA and Ryan-Einot-Gabriel-Welsch F tests.